Host-Guest Interactions Between Metal–Organic Frameworks and Air-Sensitive Complexes at High Temperature - Huang, Bo; Tan, Zhe (Frontiers in Chemistry, 2021)
Host-guest chemistry of metal-organic frameworks (MOFs) attracts increasing attention owing to the extensively outstanding properties derived from MOFs-guests combinations. However, there are large difficulties on syntheses of the host-guest MOF systems with air-sensitive metal complexes. In addition, the behaviors on host-guest interactions in the above system at high temperature are not clear. This study reported the synthetic methods for host-guest system of metal-organic framework and air-sensitive metal complex via a developed chemical vapor infiltration process. With the synchrotron X-ray powder diffraction (XRPD) measurements and Fourier Transform infrared spectroscopy (FTIR), the successful loadings of Fe(CO)5 in HKUST-1 and NH2-MIL-101(Al) have been confirmed. At high temperature, the structural and chemical componential changes were investigated in details by XRPD and FTIR measurements. HKUST-1 was proved to have strong interaction to Fe(CO)5 and resulted in heavy loading amount of 63.1 wt%, but too strong interaction leaded to deformation of HKUST-1 sub-unit under heating conditions. While NH2-MIL-101(Al) has weaker interaction and be chemically inert to Fe(CO)5 at high temperature.